Determinação antecipada de falha (AFD) para a identificação de falhas potenciais no projeto de produtos: uma comparação com a análise de modo e efeitos de falha (FMEA) - Silva, Renan Favarão da (2017)
Many skills are required for the success of engineers in product development. The constant launch of new products, coupled with the increasing demands of customers and users, requires systematic and proactive approaches to design engineering. Because many faults have premature origins in the development cycle, failure mode identification tools are used to prevent such occurrences. Even the most traditional and widespread method, the Failure Mode and Effects Analysis (FMEA), is not enough by itself. In this context, this research aimed to evaluate the potential of identification of faults by Anticipatory Failure Determination (AFD) methodology. This tool is derived from the Theory of Inventive Problem Solving (TRIZ) and recommended in the literature for encouraging systematic creativity in its approach, but its evidence of effectiveness was inexistent. Thus, in the methodology of this work, experiments were developed through a theoretical-practical mini-course on both fault prediction tools (FMEA and AFD) directed to undergraduate students in engineering for training and application of methodologies. Students are accessible and widely used in design engineering surveys for method validations. The results were collected through forms throughout the activity and supported this research. From the total of 105 students from five universities in Curitiba-PR, at a significance of 5% and accuracy of 9.5%, it was observed that both tools were well evaluated. Compared to FMEA, the AFD tool was more recommended for product development (59%), while 61% suggested FMEA for complex case resolution. Although AFD was rated as more robust (50%) and as effective as FMEA, 60% of students said that FMEA is easier. Nevertheless, in practical applications, AFD showed a better results in the identification of failures and potential causes in 71% of the cases. These results evidenced the potentialities, and also counterparts, of the AFD methodology, showing an alternative method and, still, little explored in the area of product development.